2005
DOI: 10.1016/j.ajic.2004.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of hand hygiene agents in the reduction of bacteria and viruses

Abstract: Antimicrobial handwashing agents were the most efficacious in bacterial removal, whereas waterless agents showed variable efficacy. Alcohol-based handrubs compared with other products demonstrated better efficacy after a single episode of hand hygiene than after 10 episodes. Effective hand hygiene for high levels of viral contamination with a nonenveloped virus was best achieved by physical removal with a nonantimicrobial soap or tap water alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 50 publications
(66 reference statements)
7
118
1
3
Order By: Relevance
“…11 While some authors have noted that washing hands with soap and water would take at least 60 seconds to be performed properly, 12 others have found that contact times as short as 10 seconds are effective in reducing transient hand flora. 22 In our study, only 22% of the observed hand washings met this conservative recommendation of 10 seconds. Alcoholbased hand cleansers are quicker and simpler to use and were usually used correctly in these family medicine offices.…”
Section: Discussionmentioning
confidence: 71%
“…11 While some authors have noted that washing hands with soap and water would take at least 60 seconds to be performed properly, 12 others have found that contact times as short as 10 seconds are effective in reducing transient hand flora. 22 In our study, only 22% of the observed hand washings met this conservative recommendation of 10 seconds. Alcoholbased hand cleansers are quicker and simpler to use and were usually used correctly in these family medicine offices.…”
Section: Discussionmentioning
confidence: 71%
“…Para diminuir a colonização no sítio de inserção e evitar a multiplicação de microrganismos são necessárias medidas profiláticas, que se iniciam com a higienização das mãos do profissional e a adequada preparação da pele com anti-séptico. Outro cuidado após a implantação do cateter se reporta ao tipo de curativo a ser realizado (1)(2)(3) . O canhão, conexão entre a linha vascular e o sistema de infusão, é a segunda maior fonte de infecção.…”
Section: A Aderência De Microrganismos Pode Serunclassified
“…A contaminação de cateter venoso é a principal causa de infecções sangüíneas intrahospitalares, que são responsáveis pelo aumento da mortalidade (1) . Fatores de risco para infecções relacionadas a tais cateteres incluem a trombogenicidade do material, a duração prolongada da cateterização e o local do acesso vascular, a técnica e a assepsia na inserção, a prévia higienização das mãos do profissional na instalação e/ou no manuseio, além dos fatores relacionados ao paciente, como a idade e a presença de co-morbidades (1)(2)(3) . A seleção do local para a inserção do cateter vascular periférico pode minimizar o risco de infecção.…”
Section: Introductionunclassified
“…309 Various 70% alcohol solutions (ethanol, n-propanol, isopropanol) were tested against a surrogate of norovirus and ethanol with 30-second exposure demonstrated virucidal activity superior to the others. 310 In a recent experimental study, ethyl alcohol-based products showed significant reductions of the tested surrogate for a non-enveloped human virus; however, activity was not superior to non-antimicrobial or tap/faucet water controls 311 . In general, ethanol has greater activity against viruses than isopropanol 70 .…”
Section: Alcoholsmentioning
confidence: 99%